Visions of a senceless war - Kingman, Santiago (2023)
The Russian invation to Ukraine has to be contextualized on the current phase of the capitalism, its state of productive and financial constant crisis and the sharpening of the war for the control of the consumer market. But it suggests an integral look of the sense of the era, therefore, of the different spirits that encourages it. On the other hand, it presents a glimpse of the ways that the blocks of global power build the legitimation of its political and military operations when they dispute the territories and countries under their rule and the particularity of this legitimations in Ukraine. Although it is a political and military conflict, the United States and Russia are playing a rebalance on a global scale, however, in the context of a catastrophe, the unleashing of a host of consequences was not expected, which could lead to a reorganization of the world economic, technological, political and military spheres. It is suggested the hypothesis that Europe is the one who will lose the most, and even could be diluted on the game of others. China Will try, evidently, to be the winner. But the creation of an integral global reordering, doesn’t imply a fairer, more pacific, more democratic new world order, in which the subordinate countries have a voice and a vote, but, on the contrary, one more authoritarian, with even more imposing power blocks, with the menace of war always present, and with negative consequences for the planet and its inhabitants.